Laju pertumbuhan benih ikan jelawat (Leptobarbus hoevenii Blkr.) dengan pemberian pakan berbasis tepung maggot - Khotimah, Husnul; Yanti, Ari Hepi; Setyawati, Tri Rima; Kustiati, Kustiati (Jurnal Biologi Udayana, 2023)
Hoven’s carp or the mad barb ( Leptobarbus hoevenii Blkr.) is a species of local fish with slow growth. Maggot is a phase of the insect life cycle that can be developed as feed. Maggot in the form of flour is known to have a high protein content which can stimulate fish growth. This study aims to determine the growth rate of specific length (LPPS), growth rate of specific weight (LPBS), and the survival rate of jelawat fish juvenille treated with control feed (A), feed based on unfermented maggot flour (B) and feed based on fermented maggot flour (C). Based on the results, jelawat fish juvenille have the highest LPPS 0.88±0.04% and the highest LPBS 0.71±0.01% and the juvenille survival rate was 100% in treatment C, followed by treatment B with 0,49±0,04% of LPPS and 0.39±0.01% of LPBS and 95% of juvenille survival rate. The lowest growth was experienced by juvenille on control feed treatment (A) with 0.38%±0.01 of LPPS, 0.28±0.01% of LPBS, and 75% of  juvenille survival rate. Based on this, the use of fermented maggot flour in feed has a significant effect on the growth rate of jelawat fish juvenille%.